Audit Report Lag and Its Determinants - Shofiyah , Lilik; Wilujeng Suryani, Ani (KnE Social Sciences, 2020)
Audit report lag is an important issue because it can affect the timeliness of accounting information that is used by internal and external users for their decision making. This study aims to examine the influence of profitability, solvency, company size, and the reputation of public accounting firms on the audit report lag. We collected data from 40 Indonesian mining companies annual reports from 2013 to 2017. The hypotheses were tested by using multiple regression analysis. The results show that profitability and company size have significant negative impacts on audit report lag, but solvency and reputation public accounting firm have no effect. The results of this study can be taken into consideration for companies as well as possible so that they can submit financial reports in a timely manner. Keywords: profitability, solvency, company size, reputation public accounting firm, audit report lag